Circles: the replication-recombination-chromosome segregation connection. - Barre, F; Søballe, B; Michel, B; Aroyo, M; Robertson, M; Sherratt, D (2001)
Crossing over by homologous recombination between monomeric circular chromosomes generates dimeric circular chromosomes that cannot be segregated to daughter cells during cell division. In Escherichia coli, homologous recombination is biased so that most homologous recombination events generate noncrossover monomeric circular chromosomes. This bias is lost in ruv mutants. A novel protein, RarA, which is highly conserved in eubacteria and eukaryotes and is related to the RuvB and the DnaX proteins, gamma and tau, may influence the formation of crossover recombinants. Those dimeric chromosomes that do form are converted to monomers by Xer site-specific recombination at the recombination site dif, located in the replication terminus region of the E. coli chromosome. The septum-located FtsK protein, which coordinates cell division with chromosome segregation, is required for a complete Xer recombination reaction at dif. Only correctly positioned dif sites present in a chromosomal dimer are able to access septum-located FtsK. FtsK acts by facilitating a conformational change in the Xer recombination Holliday junction intermediate formed by XerC recombinase. This change provides a substrate for XerD, which then completes the recombination reaction.